2012
DOI: 10.1007/s00430-012-0245-2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a broad spectrum of inflammation-related genes by Coxsackievirus B3 requires Interleukin-1 signaling

Abstract: A broad spectrum of inflammatory cytokines was induced by CVB3 replication via a pathway that requires IL-1 signaling. Our results suggest that IL-1ra may be used as a therapeutic agent to limit inflammation and tissue destruction in myocarditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 68 publications
0
5
0
1
Order By: Relevance
“…How much inflammatory response contributes to myocardial injury and whether tissue alteration could be avoided by a more rapid decline of inflammation is currently unknown [2]. As reported previously, mediators that may play a role in the pathogenesis of the CVB-induced myocarditis include proinflammatory cytokines such as TNF-α and IL-6 [15][16][17][18] and MMPs [19,20]. In addition, studies showed that in different cardiac-related pathologic conditions, cardiomyocytes were actively involved in cytokine biosynthesis [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How much inflammatory response contributes to myocardial injury and whether tissue alteration could be avoided by a more rapid decline of inflammation is currently unknown [2]. As reported previously, mediators that may play a role in the pathogenesis of the CVB-induced myocarditis include proinflammatory cytokines such as TNF-α and IL-6 [15][16][17][18] and MMPs [19,20]. In addition, studies showed that in different cardiac-related pathologic conditions, cardiomyocytes were actively involved in cytokine biosynthesis [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence highlighted the immunopathogenetic mechanisms responsible for the development of CVB-induced myocarditis and focused on mediators that may play a role in the pathogenesis of the disease including the proinflammatory cytokines tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) [15][16][17][18] and matrix metalloproteinases (MMPs) [19,20]. Furthermore, in the past, studies showed that in different cardiac-related pathologic conditions, such as ischemic heart disease, congestive heart failure, dilated cardiomyopathy, septic cardiomyopathy and myocarditis, cardiomyocytes were actively involved in cytokine biosynthesis [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…First strand cDNA synthesis was carried out using Super Script II (Invitrogen, Carlsbad, CA), dNTP's (Promega, Madison, WI) and Random Hexamer Primers (Fermentas, Burlington, ON). Real‐time PCR was performed in a total volume of 25 µl using Brilliant SYBR Green QPCR in an Mx 3000P instrument (Agilent Technologies, Santa Clara, CA) as described previously [Rehren et al, ]. Intron spanning primer pairs for HAdV‐B3 (E1A and hexon gene) and for HAdV‐C2 (E1A, E1B, DNA polymerase and hexon gene) are described in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Among the cytokines, increased IL-1␤ levels in the heart directly correlate with increased acute CVB3-induced myocarditis in murine model (9,29). Furthermore, a broad spectrum of inflammatory cytokines is induced by CVB3 replication via a pathway that requires IL-1 signaling (18,38). Inflammasome is a key modulator of inflammatory responses via regulating IL-1␤ release and has been demonstrated to be involved in a wide variety of inflammatory and autoimmune diseases; however, its role in CVB3-induced myocarditis is still unknown.…”
Section: Discussionmentioning
confidence: 99%